Continual Corporate Entrepreneurial Search for Long-Term Growth - Bhardwaj, Gaurab; Camillus, John C.; Hounshell, David A. (Management Science, 2006)
This paper examines how established firms conduct continual entrepreneurial search for possibilities for long-term growth. Drawing on comprehensive internal documents of the DuPont Company over a 20-year period, we develop a search process that is a departure from frequent depictions of search as local or random. Longitudinal field data show that corporate entrepreneurs follow a “moving, anchored search” for growth possibilities. Employing this framework as lens, we develop propositions. We find that corporate entrepreneurs are more likely to conduct search in new domains following events that cause them to expect future performance to change significantly and lastingly. This is in contrast to the literature that has typically modeled the initiation of search as a response to poor past performance. Because new domains are unexplored territories for corporate entrepreneurs, they utilize transitional levers that they perceive will facilitate the move from existing domains to new ones. These perceived transitional levers, however, typically prove inaccurate or incomplete. Content within domains is searched using anchors whose locations and numbers change. The combination of search process and content searched influences the particular growth possibilities discovered and created. Search and pursuit of growth possibilities is accompanied by the creation of new knowledge and new capabilities.